Combining Digital Storytelling and Health Coaching in Chronic Disease Management: A Scoping Review - Andi Sulfikar; Mulyati Mulyati; Irawati Irawati; Indah Restika BN (GLOBAL HEALTH SCIENCE GROUP, 2025)
Chronic diseases such as diabetes, hypertension, and cardiovascular conditions require ongoing and holistic management. Digital storytelling and health coaching are innovative methods that support chronic disease management. Digital storytelling enables patients to share personal experiences, enhancing their understanding and engagement. Health coaching offers personalized support to help patients achieve health goals through sustainable lifestyle changes. This scoping review aims to examine the existing literature on the use of digital storytelling and health coaching in chronic disease management. The review focuses on the potential benefits of combining these approaches and identifying research gaps. A literature search was conducted across electronic databases (PubMed, Scopus, Google Scholar) using keywords related to digital storytelling, health coaching, and chronic disease management. Studies meeting the inclusion criteria were analyzed to identify key themes and research gaps. The findings indicate that digital storytelling enhances patient understanding of their condition, promotes better communication with healthcare providers, and increases patient engagement. Health coaching effectively helps patients set and achieve health goals through a structured and personalized approach. The combination of these methods provides a more holistic approach to chronic disease management. Integrating digital storytelling and health coaching provides a personalized, empathetic, and coordinated method for addressing chronic illnesses. However, further research is required to enhance integration strategies and evaluate the sustained impact of these methods across different long-term health conditions.